Metabolic and molecular analysis of nonuniform anthocyanin pigmentation in tomato fruit under high light. Issue 1 (1st May 2019) - Zhang, Yanjie; Li, Yan; Li, Wanping; Hu, Zongli; Yu, Xiaohui; Tu, Yun; Zhang, Min; Huang, Jinyong; Chen, Guoping
Abstract: Pigment intensity and patterns are important factors that determine the nutritional and market values of tomato fruits. The acropetal manner of light-dependent anthocyanin accumulation with the highest levels at the stem end of the fruit makes Pro35S:BrTT8 tomato plants an ideal system for investigating the effects of light intensity on anthocyanin biosynthesis. Extensive transcript analyses indicate that anthocyanin pigmentation in Pro35S:BrTT8 plants under high light might be coordinately regulated by the exogenous protein BrTT8 and endogenous proteins SlAN2 and SlMYBL2. Furthermore, yeast two-hybrid assays showed that BrTT8 could interact efficiently with SlAN2, SlMYBL2, and SlAN11. Moreover, the physical interaction between BrTT8 and SlAN2 was validated by FRET. Simultaneous overexpression of SlAN2 and BrTT8 activated significant anthocyanin biosynthesis in infiltrated tobacco leaves. In addition, the ability of SlMYBL2 to suppress anthocyanin accumulation was also demonstrated in infiltrated tobacco leaves. Altogether, these results prove that tissue-specific assemblage of the heterogeneous MYB-bHLH-WD40 complex consisting of SlAN2, BrTT8 and SlAN11 triggers nonuniform anthocyanin accumulation in tomato fruit under high light. Additionally, it is proposed that a negative-feedback loop fulfilled by SlMYBL2 also participates in the regulation of anthocyanin production. Metabolism: the protein regulators of nutrient accumulation: Protein regulators of anthocyanin production have been identified in tomato and tobacco plants. Endogenously produced anthocyanins confer protective benefits to plants, and there is growing evidence of their health benefits to humans. Researchers from China, led by Chongqing University's Guoping Chen, analyzed tobacco and genetically modified tomato plants grown under high- and low-light conditions to discern the cellular processes modulating anthocyanin production. The team found a number of interacting metabolites that promoted anthocyanin, in particular a complex of three proteins, and evidence of a negative-feedback loop to prevent over-accumulation. These results provide insight into the biosynthesis of plant nutrients, could inform future efforts to genetically engineer more nutritious and valuable fruit, and also validates the team's mutant tomato plant as a strong model to study anthocyanin production. Highlight: High-light-induced nonuniform anthocyanin pigmentation in fruits of Pro35S:BrTT8 tomato plants is due to region-specific assemblage of a functional MBW protein complex consisting of BrTT8, SlAN2 and SlAN11.